The Effect of Inquiry Based Learning on Students Mastery of Concept and Social Skills - Syarifuddin, Syarifuddin (JTAM (Jurnal Teori dan Aplikasi Matematika), 2023)
Inquiry Based Learning is a learning strategy that provides space for students to carry out investigations. This study was conducted to test whether there is a positive effect of Inquiry based learning on mastery of concepts and student social skills. The participant used was students of Early Childhood Islamic Education which consisted of 31 people for the experimental class and 30 people for the control class. The type of research used was quasi-experimental design. To test the analysis prerequisites using the data normality test using the Kolmogorov-Smirnov technique and the variance homogeneity test. Furthermore, to analyze hypothesis testing data using parametric statistics, with Analysis of variance techniques (ANOVA). Based on the results of hypothesis testing concluded that there are significant differences in the mastery of the concept of the experimental group students with the control group. then there are significant differences in the social skills of the experimental group students with the control group. The implication of this study is that the use of Inquiry based learning positively influences the mastery of concepts and student social skills and provides good experience to prospective Early Childhood Education teacher students collaborating on various investigations in solving problems.